The Veil: Women Writers on its History, Lore, and Politics. Edited by Jennifer Heath. University of California Press2008. Pp. 360. $21.95. ISBN: 0-520-25518-6. - Gray-Hildenbrand, Jenna (Journal of law and religion, 2009)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0748081400001491/resource/name/firstPage-S0748081400001491a.jpg